Analysis of the sustainability status of community-based drinking water supply in Kapongan District, East Java - Andriyanto, Nur; Suheri, Asep; Soesanta, Prabawa Eka (Universitas Pakuan, 2023)
Ensuring the availability and sustainability of clean water is a key focus of the United Nations Sustainable Development Goals (SDGs) and has emerged as a significant concern for both central and local governments in Indonesia. In the Kapongan District of Situbondo Regency, the government's PAMSIMAS Programme is a proactive initiative designed to secure safe access to drinking water for the community. Within this district, two villages, Landangan and Pokaan, have successfully implemented community-based drinking water provision. The ongoing sustainability of these water supply systems in these villages is pivotal for meeting the continuous drinking water needs of the community, necessitating a comprehensive investigation into its sustainability. The primary objective of this study is to assess the sustainability status of community-based drinking water provision within the ongoing PAMSIMAS program in Kapongan District. The dimensions under consideration encompass environmental, social, economic, technological, and institutional aspects. Employing a quantitative approach, the research utilizes the Rap-SPAM analysis method, a modification of Rapfish, with primary data collected through surveys, observations, and interviews. Additionally, secondary data is acquired through an extensive literature review and consultation with various related agencies. The assessment results reveal a sustainability index of 58.92, classifying it as reasonably sustainable. The Multi-Dimensional Scaling (MDS) model produced Stress values ranging from 0.15 to 0.18 and R2 values between 0.93 to 0.94. The variance between the MDS index and Monte Carlo analysis is less than 5%. In conclusion, this study finds that the community-based water supply facilitated by the PAMSIMAS program in Kapongan District demonstrates a reasonably sustainable status. To enhance its sustainability, there is a need to prioritize and improve dimensions with lower sustainability index values in a holistic manner.ABSTRAKMemastikan ketersediaan dan keberlanjutan air bersih merupakan fokus utama Tujuan Pembangunan Berkelanjutan (SDGs) PBB dan menjadi perhatian besar bagi pemerintah pusat dan daerah di Indonesia. Di Kecamatan Kapongan Kabupaten Situbondo, Program PAMSIMAS yang dicanangkan pemerintah merupakan inisiatif proaktif yang dirancang untuk menjamin akses yang aman terhadap air minum bagi masyarakat. Di kabupaten ini, Desa Landangan dan Pokaan telah berhasil menerapkan penyediaan air minum berbasis masyarakat. Keberlanjutan sistem pasokan air di desa-desa ini sangat penting untuk memenuhi kebutuhan air minum masyarakat secara berkelanjutan, sehingga memerlukan kajian komprehensif. Tujuan dari penelitian ini untuk menilai status keberlanjutan penyediaan air minum berbasis masyarakat dalam program PAMSIMAS yang sedang berjalan di Kecamatan Kapongan. Dimensi yang dipertimbangkan meliputi aspek lingkungan, sosial, ekonomi, teknologi, dan kelembagaan. Dengan menggunakan pendekatan kuantitatif, penelitian ini menggunakan metode analisis Rap-SPAM, modifikasi dari Rapfish, dengan data primer yang dikumpulkan melalui survei, observasi, dan wawancara. Selain itu, data sekunder diperoleh melalui penelusuran literatur yang ekstensif dan konsultasi dengan berbagai lembaga terkait. Hasil kajian menunjukkan indeks keberlanjutan sebesar 58,92 yang tergolong cukup berkelanjutan. Model Multi-Dimensional Scaling (MDS) menghasilkan nilai Stress yang berkisar antara 0,15 hingga 0,18 dan nilai R2 antara 0,93 hingga 0,94. Perbedaan antara indeks MDS dan analisis Monte Carlo kurang dari 5%. Kesimpulannya, penelitian ini menemukan bahwa pasokan air berbasis masyarakat yang difasilitasi oleh program PAMSIMAS di Kabupaten Kapongan menunjukkan status yang cukup berkelanjutan. Untuk meningkatkan keberlanjutannya, terdapat kebutuhan untuk memprioritaskan dan memperbaiki dimensi dengan nilai indeks keberlanjutan yang lebih rendah secara holistik.